On-line immobilized trypsin microreactor for evaluating inhibitory activity of phenolic acids by capillary electrophoresis and molecular docking. (25th April 2020) - Zhang, Hao; Wu, Zhao-Yu; Wang, Yin-Zhen; Zhou, Dong-Dong; Yang, Feng-Qing; Li, De-Qiang
Highlights: A simple, economical and fast on-line immobilized trypsin microreactor is developed. The develop method is applied for evaluating inhibitory activity of phenolic acids. The structure-activity relationship of phenolic acids on trypsin is discussed. Abstract: Phenolic acids, which are important aromatic secondary metabolites, are widely distributed in plant foods. In this study, a simple, economical and fast on-line immobilized trypsin microreactor was developed for evaluating the inhibitory activity of phenolic acids by capillary electrophoresis. The Michaelis-Menten constant ( K m ) of immobilized trypsin was determined as 0.99 mM, and the half-maximal inhibitory concentration (IC50 ) and inhibition constant ( K i ) of benzamidine were measured as 3.39 and 1.68 mM, respectively. Then, the developed strategy was applied to investigate the inhibitory activity of six phenolic acids on trypsin. The results showed that gallic acid, caffeic acid and ferulic acid had high inhibitory activity at concentration of 150 μM. Molecular docking results illustrated that gallic acid, caffeic acid and ferulic acid can interact indirectly with the catalytic and substrate-binding sites of trypsin. The developed strategy is an effective tool for evaluating inhibitory activity of phenolic acids on trypsin.